Redox imbalance induced by docetaxel in the neuroblastoma SH-SY5Y cells: a study of docetaxel-induced neuronal damage. (1st January 2021) - Micheli, Lucia; Collodel, Giulia; Moretti, Elena; Noto, Daria; Menchiari, Andrea; Cerretani, Daniela; Crispino, Sergio; Signorini, Cinzia
ABSTRACT: Objectives: In cancer survivors, chemotherapy-associated adverse neurological effects are described as side effects in non-targeted tissue. We investigated the role of redox-imbalance in neuronal damage by a relative low dose of Docetaxel (DTX). Methods: The neuroblastoma cells (SH-SY5Y cells) were exposed to DTX at a dose of 1.25 nM for 6 h. Antioxidant defenses (i.e. ascorbic acid, glutathione, and catalase) and lipid oxidation products (i.e. F2 -isoprostanes) were evaluated. To investigate cell ultrastructure and tubulin localisation, transmission electron microscopy (TEM) and immunofluorescence techniques were applied. Results: In the SH-SY5Y cells, DTX induced a significant reduction of total glutathione ( P < 0.001) and ascorbic acid ( P < 0.05), and an increase in both total F2 -Isoprostanes ( P < 0.05) and catalase activity ( P < 0.05), as compared to untreated cells. Additionally, TEM showed a significant increase in cells with apoptotic characteristics. Immunolocalisation of tubulin showed a compromised cytoskeletal organisation. Discussion: The investigated sublethal dose of DTX, to which non-targeted cells may be exposed throughout the duration of chemotherapy treatment, induces a redox imbalance resulting in a specific modulation of the antioxidant response. This study provides new insights into DTX-induced cellular mechanisms useful for evaluating whether the concomitant use of antioxidants associated with chemotherapy mitigates chemotherapy side effects in cancer survivors.